Оцінка майнового стану підприємств в системі забезпечення фінансового менеджменту - Захарова, Наталя Юріївна; Захарова, Наталья Юрьевна; Zakharova, Natalia (My University, 2018)
UK: Розглянуто особливості формування статутного капіталу і майна підприємств різних організаційно правових форм господарювання. Виділено основні складові джерел фінансування та активів підприємств. Обґрунтовано підхід до формування агрегованого балансу, визначення показників майнового стану підприємств та здійснено їх розрахунок на прикладі підприємств аграрного сектору економіки. Окреслено основні напрями покращення майнового стану підприємств у сучасних умовах господарювання. EN: The author established that unstable environmental conditions reduced the possibility of attracting resources for the development of business entities, which is particularly relevant to the agrarian sector. The specifics of the latter's activities are related to the need to invest a significant amount of funds to form a certain amount of current assets for a limited period of time. Due to the negative influence of various factors, among which one can distinguish inflation processes, devaluation of hryvnia, etc., own financial resources are often lacking even for current needs. So, for many enterprises in the agrarian sector of the economy, the replacement of outdated fixed assets became impossible. At the same time, attraction of borrowed resources is unjustified at present, since the payment for their use far exceeds the efficiency of economic activity, that is, the profit per unit of invested capital is much less than interest on the loan. Identify opportunities for further development of the enterprise can be based on a comprehensive assessment of the financial state in the context of its individual components, namely, financial stability, liquidity, profitability, business activity, property state. It is substantiated that the basis of real estate valuation is the formation of the aggregated balance sheet, which allows to provide an objective assessment of the situation existing at the enterprise in relation to the sources of financing and the corresponding composition of assets. At the same time, the analysis allows to detect changes occurring in the dynamics and structural changes that are observed in the enterprise. It has been established that the assessment of the property state gives an answer to the question of the suitability of the main means of the enterprise for use in the economic process and their updating and retirement. It is established that the use of the approaches presented in the work will allow to react promptly to changes in the structure of assets and liabilities by substantiating a set of measures aimed at improving the financial state of enterprises in general and property in particular.
Evaluation of the property state of the enterprise in the financial management supply system
Keywords: майновий стан підприємства; статутний капітал; власний капітал; необоротні активи; оборотні активи; основні засоби; агрегований баланс; коефіцієнт зносу; property state of the enterprise; authorized capital; equity; non-current assets; current assets; fixed assets; aggregated balance; depreciation coefficient